The Influence of Psychosocial Learning Environments on Students’ Self-Efficacy Beliefs in English Language Learning - Lemma W/Michael Gelete; Tamene Kitila Dhaba (Edukasi, 2022)
The overarching aim of this study was to investigate whether the psychosocial learning environments of English classes influence students’ self-efficacy beliefs in English language. In order to achieve this purpose, correlational design was adopted. The study involved the gathering of data through What Is Happening In this Class and Self-Efficacy Belief questionnaires from 371 samples. Simple random sampling was used to draw the samples from the population. Simple correlations, multiple regression and standardized regression coefficients were computed to analyze the collected data. The results depict that all of the six psychosocial learning environment aspects were significantly related to students’ self-efficacy beliefs. The set of learning environment scales also significantly influence students’ self-efficacy beliefs. Among the six aspects, student involvement, task orientation and student cohesiveness contributed to the influence on students’ self-efficacy beliefs. The influence of the task orientation aspect was the strongest; this is followed by student cohesiveness and student involvement. This implies that students tend to have high self-efficacy beliefs in English language when there were more task-oriented and cohesive classroom environment and when students were encouraged to involve themselves well in class activities. Hence, the psychosocial learning environments of English classes need improvement to enhance students’ self-efficacy beliefs towards English language. In particular, the learning environment aspects of task orientation, student cohesiveness and involvement play a pivotal role in enhancing students’ self-efficacy beliefs in English learning.